Technology innovation in library: a bibliometric review - Margono, Hendro; Rasyid, Rizka Adristi; Setiyarini, Melina Dewi (Universitas Negeri Yogyakarta, 2024)
Technological innovation is changing libraries and how libraries operate. This study presents a bibliometric analysis to identify key patterns and trends in research on technological innovation in libraries, based on the publication of papers indexed in Web of Science from 2019 to 2023. A total of 433 documents from 342 sources were analyzed using Biblioshiny and VOSViewer software. The results show an increasing interest in this research domain, despite a negative annual publication growth rate of -32.33% in recent years. The IEEE Winter Conference on Computer Vision Applications and the IEEE Symposium on Security and Privacy were the most productive sources.